P53 pathway changes and their influence on chronic lymphoproliferative diseases pathogenesis - P. M. Kondratovskiy; A. I. Dubikov; A. Yu. Doroshevskaya (Онкогематология, 2014)
The role of p53 family proteins, both in the pathogenesis of chronic lymphoproliferative disorders, and in aspects of the growi ng interest in thetherapeutic potential of so-called small molecules capable of influencing the regulatory "relationship" of p53, MDM2, p21 and P UMA is currently actively debated. The article is an attempt to summarize the data on experimental tumor and mouse models and availablen ithe l iterature results of studies using human lymphoid tumors. Prognostic significance of p53 family proteins expression in lymphoproliferativ e diseases and possible therapeutic approaches using the features of the p53 relationship with regulators and effectors genes are considered.